Security and profit in China's energy policy : hedging against risk - Tunsjø, Øystein (Contemporary Asia in the world., 2013)
China has developed sophisticated hedging strategies for managing the international petroleum market, maintaining a favorable energy mix, pursuing overseas equity oil production, building a state-owned tanker fleet and strategic petroleum reserve, establishing cross-border pipelines, and diversifying its energy resources and routes. Though it cannot be?secured," China's energy security can be?insured" by marrying government concern with commercial initiatives. This book identifies the interrelationship between security and profit that better describes China's energy-security policy.